A method for determining the proportion of conductive agent in a double-layer distributed lithium-ion battery electrode

By conducting multiple tests and fittings on the double-layer structure lithium-ion battery electrode plate, the conducting agent ratio is determined, and the problem of undetermined component ratio in the prior art is solved, and a comprehensive evaluation and optimization of battery performance is achieved.

CN114914560BActive Publication Date: 2024-12-13WUHAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210343561.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-04-02
Publication Date
2024-12-13
Estimated Expiration
2042-04-02

AI Technical Summary

Technical Problem

The prior art cannot effectively determine the optimal component ratio between the electrodes of the two-layer structure lithium-ion battery, resulting in insufficient comprehensive and accurate battery performance evaluation, and evaluation based on energy density and power density alone is not enough.

Method used

After activation, constant-magnification cycle test, gradient-magnification performance test, AC impedance test and cyclic voltammetry test are performed, characteristic parameters are extracted, fitted to determine the conductor ratio, combined with the MATLAB fitting toolbox, the optimal ratio is obtained Determine the ratio of conductive agent.

Benefits of technology

The comprehensive performance evaluation of the electrode sheet of the double-layer structure lithium-ion battery is achieved, and the relatively excellent gradient conductive agent distribution ratio is obtained, which improves the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114914560B_ABST
    Figure CN114914560B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for determining the proportion of a conductive agent in a double-layer distributed lithium-ion battery pole piece. By manufacturing a lithium iron phosphate positive pole piece with a double-layer distribution of a conductive agent, and manufacturing it into a battery, the battery is subjected to formation activation, constant rate cycle test, rate performance test, AC impedance test, and volt-ampere cycle test, the difference between battery samples manufactured by pole pieces with different conductive distributions can be obtained, and the lithium ion diffusion coefficient of the battery can also be calculated. The present invention can obtain a relatively excellent gradient conductive agent distribution ratio by using the weighted evaluation method through the above test test and comprehensively considering various performances.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of lithium ion batteries, and in particular relates to a method for determining the proportion of a conductive agent in a double-layer distributed lithium ion battery pole piece. Background Art

[0002] At present, lithium-ion batteries have been widely used in various consumer electronic products, electric vehicles and energy storage systems because they have advantages over other systems of batteries, such as high energy density, long cycle life and no memory effect. Compared with other types of batteries, such as ternary lithium-ion batteries, lithium iron phosphate batteries have better safety and cycle performance and are widely used in the field of commercial vehicles, but their energy density is low, and how to improve their energy density has always been a hot research issue.

[0003] The components of lithium-ion batteries generally include: positive electrode materials, positive electrode current collectors, negative electrode materials, negative electrode current collectors, separators, electrolytes and external coatings (cylindrical steel shells, square aluminum shells and aluminum-plastic composite films), etc. Among them, the type and ratio of positive and negative electrode materials have a great influence on the final capacity of the battery. For materials of various systems, the capacity that can be released is restricted by the physical and chemical properties of the materials themselves, and the energy density of the battery cannot be increased infinitely. Therefore, the current way to improve the energy density of the battery is to add other components to the electrode active materials to improve the conductivity and ion diffusion capacity of the active materials to increase the energy released by the electrode materials.

[0004] Patent CN 109585779 A discloses a method for preparing a lithium-ion battery pole piece, wherein the active material distribution of the positive electrode plate of the lithium-ion battery is a double-layer structure, which is composed of a current collector aluminum foil, a first layer of active material coating and a second layer of active material coating. The components of the two layers of active materials are different, and the thickness of the first layer of active material coating is greater than that of the first layer; similarly, the negative electrode plate also has such a structure. Preparing the battery pole piece into a battery pole piece can increase the power density of the battery without significantly reducing the energy density of the battery, thereby taking into account both the energy density and power density of the battery. However, the method described cannot determine an optimal component ratio, and the specific effect of improving the battery performance of the pole piece structure is not clearly quantified. It is not enough to evaluate the superiority of the pole piece only from the energy density and power density.

[0005] Patent CN 112436103 A discloses a double-layer structure pole piece and its preparation method and application. The lithium-ion battery pole piece is also a double-layer structure. By adjusting the ratio of the binder in the upper and lower active materials, the peeling force between the active material of the pole piece and the current collector can be improved, the internal resistance can be reduced, and the cycle performance of the battery can be improved. However, the method described still cannot determine an optimal component ratio, nor does it propose a better evaluation method.

[0006] It can be seen that for double-layer lithium-ion battery electrodes, there are certain differences in the components between the layers, and this difference will lead to differences in various aspects of battery performance. It is not enough to judge the superiority of a certain component structure from only one aspect. A comprehensive evaluation is required through scientific experimental testing methods and calculation methods. Summary of the invention

[0007] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for determining the proportion of conductive agent in a double-layer distributed lithium-ion battery electrode. The method can obtain the differences between battery samples manufactured from electrodes with different conductive distributions, and can also calculate the lithium ion diffusion coefficient of the battery, thereby obtaining a more excellent gradient conductive agent distribution ratio.

[0008] The purpose of the present invention is achieved through the following technical solutions:

[0009] A method for determining the proportion of a conductive agent in a double-layer distributed lithium-ion battery electrode comprises the following steps:

[0010] (1) Lithium-ion battery electrodes with different double-layer distributions are made into batteries. After the batteries are activated, constant rate cycle test, gradient rate performance test, AC impedance test and cyclic voltammetry test are performed on the batteries. Characteristic parameters are extracted from each test result, normalized, and then weights are added as the evaluation scores under the test results. Finally, the scores of each item are combined to obtain the total score under the ratio;

[0011] (2) The conductive agent ratio of lithium-ion battery electrodes with different double-layer distributions is taken as the independent variable x, and the corresponding total score is taken as the dependent variable. After fitting, a fitting curve is obtained. The value of the x-axis corresponding to the maximum value of the curve is the optimal ratio. The optimal ratio is used to determine the proportion of the conductive agent when preparing the battery electrode;

[0012] The characteristic parameters include characteristic parameter 1, characteristic parameter 2, characteristic parameter 3, characteristic parameter 4 and characteristic parameter 5, wherein characteristic parameter 1 is the capacity maximum of low-rate charge and discharge in the formation process, characteristic parameter 2 is the variance of the curve of the constant-rate cycle test, characteristic parameter 3 is the variance of the curve of the gradient rate performance test, characteristic parameter 4 is the diffusion coefficient measured by the AC impedance test, and characteristic parameter 5 is the redox peak width of the curve of the cyclic voltammetry test.

[0013] Preferably, in step (2), the MATLAB fitting toolbox is used for fitting, and a fitting curve is obtained after fitting.

[0014] Preferably, in step (1), the lithium-ion battery pole pieces with different double-layer distributions are made into button batteries.

[0015] Preferably, in the formation activation, the current rate of constant voltage charging and constant current discharging is set to 0.1C, the cut-off rate is set to 0.05C, and the charge and discharge voltage range is set to 2 to 3.65V, wherein the specific rate current size is calculated based on the actual weighing of the battery electrode.

[0016] Preferably, in the constant rate cycle test, the current rate is set to 0.5C, and the number of cycle charge and discharge is 100.

[0017] Preferably, in the gradient rate performance test, the current rate is set to 7 operating conditions, namely, 0.3C, 0.5C, 0.8C, 1C, 1.5C, 2C and 0.3C, and after 10 cycles at each rate, the next rate condition is entered.

[0018] Preferably, during the AC impedance test, an electrochemical workstation is used for testing, the scanning speed is set to 0.5 mV / s, the scanning voltage range is 2.5 to 4.2 V, and the scanning frequency is 10 kHz to 10 mHz.

[0019] Preferably, in the cyclic voltammetry test, the scan rate is set to 0.5 mV / s and the scan voltage range is 2.5 to 4.2V.

[0020] Preferably, the ambient temperature for the constant rate cycle test, gradient rate performance test, AC impedance test and cyclic voltammetry test is 25°C.

[0021] Preferably, the positive electrode active material of the button battery is at least one of lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide and nickel cobalt manganese oxide; the negative electrode material of the button battery is graphite, and the positive electrode current collector of the button battery is aluminum foil and the negative electrode current collector is copper foil.

[0022] When preparing the positive electrode material of the button battery, polyvinylidene fluoride (PVDF) is used as a binder, N-methylpyrrolidone (NMP) is used as a solvent, and at least one of acetylene black, carbon nanotubes and graphene is used as a conductive agent; the positive electrode active material of the button battery accounts for 80% to 95wt% of the mass fraction of the positive electrode material, the conductive agent accounts for 2.5% to 12wt% of the mass fraction of the positive electrode material, the binder accounts for 2.5% to 8wt% of the mass fraction of the positive electrode material, and the mass of the solvent is 3 times that of the solute.

[0023] Preferably, the weight of the characteristic parameter 1 is 0.15; the weight of the characteristic parameter 2 is 0.2; the weight of the characteristic parameter 3 is 0.2; the weight of the characteristic parameter 4 is 0.05; the weight of the characteristic parameter 5 is 0.2; and the battery is a button battery.

[0024] Compared with the prior art, the beneficial effects of the present invention include:

[0025] Under constant temperature conditions, through low-rate charge and discharge, constant-rate charge and discharge cycle tests, rate performance tests, AC impedance tests and volt-ampere cycle tests in the formation process, the capacity, aging characteristics, aging characteristics at different rates, impedance characteristics and volt-ampere characteristics of batteries made of electrode sheets with different component proportions can be obtained, and the lithium ion diffusion coefficient can be calculated, so as to comprehensively judge which component of double-layer structure battery electrode sheet can produce the best overall performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 Schematic diagram of the structure of the double-layer electrode material layer of sample 1, wherein A is the first electrode material layer and B is the second electrode material layer.

[0027] Figure 2 This is the relationship curve between voltage and specific capacity during the formation process of battery samples 1 to 5.

[0028] Figure 3 The cyclic voltammetry curves of battery samples 1 to 5 are shown in FIG. 5 . The scanning rate is set to 0.5 mV / s and the scanning voltage range is 2.5 to 4.2 V.

[0029] Figure 4 The aging characteristic diagram of battery samples 1 to 5 in constant rate charge and discharge cycle test.

[0030] Figure 5 The aging characteristic diagram of battery samples 1 to 5 in cycle tests at gradient rates.

[0031] Figure 6 The AC impedance spectra of battery samples 1 to 5 after formation at a current rate of 0.1C.

[0032] Figure 7 It is a first-order RC equivalent circuit with Weber impedance.

[0033] Figure 8 is the real part of impedance Z re With ω -0.5 The actual and fitted linear relationship.

[0034] Fig. 9 It is the performance comprehensive score of battery samples 1 to 5 and the fitting curve of the total score. DETAILED DESCRIPTION

[0035] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific implementation cases described herein are only used to explain the present invention and are not used to limit the present invention.

[0036] The preparation process of the positive electrode sheet of the button battery is as follows:

[0037] (1) Preparation of lithium-ion battery positive electrode sheets with different double-layer distributions: Lithium iron phosphate powder, acetylene black, PVDF and NMP were mixed to prepare slurries A and B with different conductive agent contents. The mass ratios of the slurries of samples 1 to 5 were 399.5:390.5, 399:391, 397:393, 395:395 and 393:397, respectively. Fix the aluminum foil on the glass plate, evenly apply the prepared slurry A on the aluminum foil, put the electrode sheet into a vacuum thermostat, vacuum dry at 80°C, and dry for 12 hours to obtain the first electrode material layer; evenly apply the prepared slurry B on the first layer of electrode material, put the electrode sheet into a vacuum thermostat again, vacuum dry at 80°C, and dry for 12 hours to obtain the second electrode material layer; adjust the gap between the two rollers of the roller press, send the electrode sheet into the roller press for multiple rolling, and adjust the gap between the rollers between 40 and 60 microns. Finally, a 42-micron thick electrode sheet is obtained, in which the thickness of the aluminum foil is 26 microns and the thickness of the electrode material is 16 microns. Five positive electrode sheet samples are prepared here, in which the ratios of slurry A and slurry B are:

[0038] Sample 1:

[0039] Slurry A: The mass ratio of lithium iron phosphate powder, acetylene black, PVDF and NMP is 80:9.5:10:300;

[0040] Slurry B: The mass ratio of lithium iron phosphate powder, acetylene black, PVDF and NMP is 80:0.5:10:300;

[0041] Sample 2:

[0042] Slurry A: The mass ratio of lithium iron phosphate powder, acetylene black, PVDF and NMP is 80:9:10:300;

[0043] Slurry B: The mass ratio of lithium iron phosphate powder, acetylene black, PVDF and NMP is 80:1:10:300.

[0044] Sample 3:

[0045] Slurry A: The mass ratio of lithium iron phosphate powder, acetylene black, PVDF and NMP is 80:7:10:300;

[0046] Slurry B: The mass ratio of lithium iron phosphate powder, acetylene black, PVDF and NMP is 80:3:10:300.

[0047] Sample 4:

[0048] Slurry A: The mass ratio of lithium iron phosphate powder, acetylene black, PVDF and NMP is 80:5:10:300;

[0049] Slurry B: The mass ratio of lithium iron phosphate powder, acetylene black, PVDF and NMP is 80:5:10:300.

[0050] Sample 5:

[0051] Slurry A: The mass ratio of lithium iron phosphate powder, acetylene black, PVDF and NMP is 80:3:10:300;

[0052] Slurry B: The mass ratio of lithium iron phosphate powder, acetylene black, PVDF and NMP is 80:7:10:300.

[0053] (2) Preparation of button cells: The prepared lithium-ion battery positive electrode sheets with different double-layer distributions and metal lithium sheets were made into 2032-type button cells. The electrolyte consisted of 1.0 mol / L LiPF6 / EC+DEC (volume ratio of 1:1), and the injection volume was 60 μL. They were respectively recorded as battery samples 1 to 5; samples 1 to 5 corresponded to battery samples 1 to 5, respectively.

[0054] Determine the current rate

[0055] Since the battery is made in the laboratory, its actual capacity is unknown, so the battery charge and discharge rate current cannot be determined. Therefore, the current rate during the formation process is calculated according to the empirical formula, which is as follows:

[0056]

[0057] In the formula, I 1C is the current size of the battery at 1C rate charge and discharge in the theoretical case, α is the proportion of active materials, φ is the coefficient of converting theoretical specific capacity into actual specific capacity, which is set to 0.9 according to the reference, M is the mass of the coating material on the positive electrode sheet, Q a is the theoretical specific capacity of lithium iron phosphate material, which is 170 mAh / g, and t is the time constant, which is 1 h.

[0058] The rate current size of the formation process is calculated by the above formula. After formation, the actual capacity of the battery can be obtained. Subsequent charge and discharge tests can determine the charge and discharge rate current size of the battery based on the capacity size after formation.

[0059] Battery testing equipment: Xinwei's CT4008 series battery testing equipment is used for battery formation and cycle charge and discharge tests; CHI660E electrochemical workstation is used for battery AC impedance analysis.

[0060] Figure 1Schematic diagram of the structure of the double-layer electrode material layer of sample 1. The structures of samples 2 to 5 are similar to that of sample 1 and will not be repeated here.

[0061] After battery samples 1 to 5 are formed and activated, the optimal gradient conductive agent distribution ratio is comprehensively evaluated and determined by performing constant current cycle test, rate performance test, AC impedance test and cyclic voltammetry test on the battery.

[0062] Figure 2 The relationship curve between voltage and specific capacity of battery samples 1 to 5 during the formation process is 0.1C, where A (9.5%) + B (0.5%) corresponds to battery sample 1; A (9%) + B (1%) corresponds to battery sample 2; A (7%) + B (3%) corresponds to battery sample 3; A (5%) + B (5%) corresponds to battery sample 4; A (3%) + B (7%) corresponds to battery sample 5. Figure 2 It can be seen from the figure that the formation effect of each sample under the condition of 0.1C small rate can more accurately derive the theoretical specific capacity of the battery. The theoretical specific capacity of lithium iron phosphate material is 170mAh / g. It can be seen that the specific capacity reflected by different battery samples is different. The larger the parameter, the higher the score. The specific capacity and score of battery samples 1 to 5 are shown in Table 1.

[0063] Table 1 Specific capacity and ratings of battery samples 1 to 5

[0064]

[0065] The calculation method of a1 and a2 in Table 1 is as follows:

[0066]

[0067] a2=0.15×a1 (2)

[0068] In the formula, a is the specific capacity of the battery during the low rate charge and discharge process, a max is the maximum value, a min is the minimum value, a1 is the normalized value, and a2 is the score after considering the weight.

[0069] Figure 3 The cyclic voltammetry curves of battery samples 1 to 5 are shown in Figure 1. The scanning speed is set to 0.5 mV / s, and the scanning voltage range is 2.5 to 4.2 V. Among them, A (9.5%) + B (0.5%) corresponds to battery sample 1; A (9%) + B (1%) corresponds to battery sample 2; A (7%) + B (3%) corresponds to battery sample 3; A (5%) + B (5%) corresponds to battery sample 4; A (3%) + B (7%) corresponds to battery sample 5. Figure 3It can be clearly seen that each sample has reduction peaks and oxidation peaks during the charge and discharge process, which reflects the extraction and embedding process of lithium ions. If the width of the oxidation peak and the reduction peak is smaller, it means that the reversibility of the battery is better, the polarization effect is smaller, the polarization internal resistance is smaller, and the battery performance is better. Therefore, the smaller the parameter, the higher the score.

[0070] Table 2 Redox peak width and score of battery samples 1 to 5

[0071]

[0072] The calculation method of b1, b2 and b3 in Table 2 is as follows:

[0073]

[0074] b2=|b1-1| (4)

[0075] b3=0.2×b2 (5)

[0076] Where b is the battery redox peak width, b max is the maximum width, b min is the minimum width, b1 is the normalized value. Since the smaller the width of the redox peak, the better the battery performance, it is necessary to transform the normalized result of b1 from equation (4) to b2, and b3 is the score after considering the weight.

[0077] Figure 4 The aging characteristics of battery samples 1 to 5 in constant rate charge and discharge cycle test, where A (9.5%) + B (0.5%) corresponds to battery sample 1; A (9%) + B (1%) corresponds to battery sample 2; A (7%) + B (3%) corresponds to battery sample 3; A (5%) + B (5%) corresponds to battery sample 4; A (3%) + B (7%) corresponds to battery sample 5. Figure 4 It can be clearly seen that during the 0.5C rate charge and discharge process of each sample, the battery capacity increases slightly in the initial stage of the cycle. This is because, during the formation process, the current rate is small and the battery active material is not fully activated. In the later stage of the cycle, different battery samples have different aging rates. This is because the polarization and ohmic internal resistance between the battery samples are different, resulting in different aging speeds. The fluctuation amplitude of the curve is different. Samples with large fluctuation amplitudes indicate that their capacity decays faster and their performance is worse. The fluctuation amplitude can select the curve variance as a characteristic evaluation indicator.

[0078] Table 3 Variance and score of constant rate aging curves of battery samples 1 to 5

[0079]

[0080] The calculation method of b1, b2 and b3 in Table 3 is as follows:

[0081]

[0082] c2=|c1-1| (7)

[0083] c3=0.2×c2 (8)

[0084] Where c is the variance of the constant rate aging curve of the battery, c max is the maximum variance, c min is the minimum variance, c1 is the normalized value. Since the smaller the variance, the better the battery capacity retention ability and the better the battery performance, the normalized result of c1 needs to be transformed from formula (7) to c2, and c3 is the score after considering the weight.

[0085] Figure 5 The aging characteristic diagram of battery samples 1 to 5 in the cycle test at gradient rates, where A (9.5%) + B (0.5%) corresponds to battery sample 1; A (9%) + B (1%) corresponds to battery sample 2; A (7%) + B (3%) corresponds to battery sample 3; A (5%) + B (5%) corresponds to battery sample 4; A (3%) + B (7%) corresponds to battery sample 5. The current rate is set to 7 conditions: 0.3C, 0.5C, 0.8C, 1C, 1.5C, 2C and 0.3C. After 10 cycles at each rate, it enters the next rate condition. Figure 5 It can be seen that the cycle performance of each sample under gradient rate is that under low rate conditions, the capacity decrease of each sample is not much different; when the rate suddenly increases, the sample with a lower conductive agent content in the first electrode material layer decreases significantly more, and the curve changes greatly. Therefore, the variance is extracted as the characteristic of the curve, and the smaller this parameter, the better.

[0086] Table 4 Variance and score of gradient rate aging curves of battery samples 1 to 5

[0087]

[0088] The calculation method of d1, d2 and d3 in Table 4 is as follows:

[0089]

[0090] d2=|d1-1| (10)

[0091] d3=0.2×d2 (11)

[0092] Where, d is the variance of the battery gradient rate aging curve, d max is the maximum variance, d minis the minimum variance, d1 is the normalized value. Since the smaller the variance, the better the battery capacity retention ability and the better the battery performance, the normalized result of d1 needs to be transformed from formula (10) to d2. d3 is the score after considering the weight.

[0093] Figure 6 The AC impedance spectra of battery samples 1 to 5 after formation at a current rate of 0.1C, where A (9.5%) + B (0.5%) corresponds to battery sample 1; A (9%) + B (1%) corresponds to battery sample 2; A (7%) + B (3%) corresponds to battery sample 3; A (5%) + B (5%) corresponds to battery sample 4; A (3%) + B (7%) corresponds to battery sample 5. The test was performed using an electrochemical workstation with a scan speed set to 0.5mV / s, a scan voltage range of 2.5 to 4.2V, and a scan frequency of 10kHz to 10mHz. Figure 6 The AC impedance characteristics of each sample can be seen in the figure. The intercept of the curve with the horizontal axis is the ohmic impedance of the battery corresponding to the high-frequency region. The mid-frequency region can be approximately regarded as a semicircle, which represents the charge transfer impedance of the battery. The low-frequency region is approximately a 45° straight line, which represents the Weber impedance of lithium ion diffusion. It can be seen from the figure that the difference in the AC impedance characteristics of different samples is mainly manifested in the mid-frequency region. From battery sample 1 to battery sample 5, the charge transfer impedance of the battery gradually increases, and the transfer resistance of lithium ions increases.

[0094] By choosing a lithium-ion battery equivalent circuit with a first-order RC loop with Weber impedance (such as Figure 7 As shown in the figure, the AC impedance diagram is fitted by equation (12), and the fitted relationship diagram is shown in the figure Figure 8 As shown, the Weber coefficient σ can be calculated by formula (12), and the calculation method is as follows:

[0095] Z re =R O +R CT +σω -0.5 (12)

[0096] In the formula, Z re is the real part of impedance, R O is the ohmic impedance, R CT is the charge transfer impedance, ω is the impedance angular frequency, and σ is the Weber coefficient.

[0097] The lithium ion diffusion coefficient D of the battery can be obtained by further calculation, and the calculation formula is as follows:

[0098]

[0099] In the formula, D is the lithium ion diffusion coefficient, R is the ideal gas constant, T is the absolute temperature of the environment, A is the surface contact area of ​​the electrode, n is the number of electron transfers, F is the Faraday constant, and c is the lithium ion concentration.

[0100] The larger the diffusion coefficient, the smaller the resistance in the battery transfer process. The Weber coefficient σ and the diffusion coefficient D of each sample, the larger the D, the higher the score, as shown in Table 5.

[0101] Table 5 Weber coefficient σ and diffusion coefficient D and scores of battery samples 1 to 5

[0102]

[0103] The calculation methods of e and e1 in Table 5 are as follows:

[0104]

[0105] e1=0.05×e (15)

[0106] Where e is the normalized value of the diffusion coefficient, and e1 is the score after considering the weight.

[0107] Combining the scores of the above five indicators, the total score is calculated according to formula (16):

[0108] f=a2+b3+c3+d3+e1 (16)

[0109] The comprehensive performance scoring results of each battery sample are shown in Table 6.

[0110] Table 6 Comprehensive performance score list of each battery sample

[0111]

[0112] Using the data in Table 6 and the conductive agent ratio of the sample as the independent variable x, the data in Table 6 is converted into the data in Table 7. The MATLAB fitting toolbox is used to fit the data in Table 7. The data is fit and the maximum value of the curve is obtained. The corresponding x-axis value is the optimal ratio, that is, the ratio of the conductive agent in slurry A to that in slurry B.

[0113] Table 7 Fitting input data

[0114] A and B conductive agent ratio x 19 9 2.333 1 0.429 Total score f(x) 0.71895 0.7825 0.6508 0.29345 0

[0115] The fitting formula is shown as follows:

[0116]

[0117] In the formula, p1, p2, p3 and q1 are unknown coefficients, which are automatically calculated by the MATLAB fitting toolbox. The relevant parameters and fitting error index coefficients and variance SSE, root mean square error RMSE and goodness of fit R 2 As shown in Table 8:

[0118] Table 8 Fitting results

[0119] Parameters / Indicators <![CDATA[p1]]> <![CDATA[p2]]> <![CDATA[p3]]> <![CDATA[q1]]> SSE RMSE <![CDATA[R 2 ]]> Numeric -0.01606 1.073 -0.4682 0.8238 0.0028 0.0504 0.9943

[0120] like Fig. 9 As shown, according to the fitting results, the optimal ratio is 8.39, that is, A (8.94%) + B (1.06%), with a score of 0.836, which corresponds to: slurry A: the mass ratio of lithium iron phosphate powder, acetylene black, PVDF and NMP is 80:8.94:10:300; slurry B: the mass ratio of lithium iron phosphate powder, acetylene black, PVDF and NMP is 80:1.06:10:300.

[0121] According to the obtained results, electrode sheets with corresponding conductive agent ratios were made, and then made into batteries. The above electrical performance tests were also carried out, and the score was 0.830, with a percentage error of 1.08%.

[0122] Through the above test experimental methods and calculation methods, the cycle characteristics, volt-ampere characteristics and AC impedance characteristics of different samples can be obtained, so as to compare and analyze the performance differences between different samples, thereby helping researchers to screen out double-layer battery electrodes with excellent impedance performance, cycle performance and high specific capacity.

[0123] This example uses a battery electrode with a gradient conductive agent distribution as an example to verify the feasibility of the method. The method is also applicable to double-layer structured battery electrodes with other component ratios. Therefore, researchers in the relevant field should understand that within the technical method described in the present invention, certain modifications, changes or replacements are all within the scope of protection of the present invention.

Claims

1. A method for determining the proportion of a conductive agent in a double-layer distributed lithium-ion battery electrode, characterized in that: The steps include: (1) Lithium-ion battery electrodes with different double-layer distributions are made into batteries. After the batteries are activated, constant rate cycle test, gradient rate performance test, AC impedance test and cyclic voltammetry test are performed on the batteries. Characteristic parameters are extracted from each test result, normalized, and then weights are added as the evaluation scores under the test results. Finally, the scores of each item are combined to obtain the total score under the ratio; (2) The conductive agent ratio of lithium-ion battery electrodes with different double-layer distributions is taken as the independent variable x, and the corresponding total score is taken as the dependent variable. After fitting, a fitting curve is obtained. The value of the x-axis corresponding to the maximum value of the curve is the optimal ratio. The optimal ratio is used to determine the proportion of the conductive agent when preparing the battery electrode; The characteristic parameters include characteristic parameter 1, characteristic parameter 2, characteristic parameter 3, characteristic parameter 4 and characteristic parameter 5, wherein characteristic parameter 1 is the capacity maximum of low-rate charge and discharge in the formation process, characteristic parameter 2 is the variance of the curve of the constant-rate cycle test, characteristic parameter 3 is the variance of the curve of the gradient rate performance test, characteristic parameter 4 is the diffusion coefficient measured by the AC impedance test, and characteristic parameter 5 is the redox peak width of the curve of the cyclic voltammetry test.

2. The method for determining the proportion of conductive agent in a double-layer distributed lithium-ion battery electrode according to claim 1, characterized in that: During the formation activation, the current rate of constant voltage charging and constant current discharging is set to 0.1C, the cut-off rate is set to 0.05C, and the charge and discharge voltage range is set to 2-3.65V.

3. The method for determining the proportion of conductive agent in a double-layer distributed lithium-ion battery electrode according to claim 1, characterized in that: In the constant rate cycle test, the current rate is set to 0.5C, and the number of cycle charge and discharge is 100.

4. The method for determining the proportion of the conductive agent in a double-layer distributed lithium-ion battery electrode according to any one of claims 1 to 3, characterized in that: In the gradient rate performance test, the current rate is set to seven operating conditions, namely, 0.3C, 0.5C, 0.8C, 1C, 1.5C, 2C and 0.3C. After 10 cycles at each rate, the next rate condition is entered.

5. The method for determining the proportion of the conductive agent in a double-layer distributed lithium-ion battery electrode according to any one of claims 1 to 3, characterized in that: During the AC impedance test, an electrochemical workstation was used for testing, with a scan rate set to 0.5 mV / s, a scan voltage range of 2.5 to 4.2 V, and a scan frequency of 10 kHz to 10 mHz.

6. The method for determining the proportion of the conductive agent in a double-layer distributed lithium-ion battery electrode according to any one of claims 1 to 3, characterized in that: In the cyclic voltammetry test, the scan rate was set to 0.5 mV / s and the scan voltage range was 2.5 to 4.2 V.

7. The method for determining the proportion of conductive agent in a double-layer distributed lithium-ion battery electrode according to claim 6, characterized in that: The weight of the characteristic parameter 1 is 0.15; the weight of the characteristic parameter 2 is 0.2; the weight of the characteristic parameter 3 is 0.2; the weight of the characteristic parameter 4 is 0.05; and the weight of the characteristic parameter 5 is 0.2; In the step (2), the MATLAB fitting toolbox is used for fitting, and a fitting curve is obtained after fitting.

8. The method for determining the proportion of the conductive agent in a double-layer distributed lithium-ion battery electrode according to any one of claims 1 to 3, characterized in that: The ambient temperature for the constant rate cycle test, gradient rate performance test, AC impedance test and cyclic voltammetry test is 25°C.

9. The method for determining the proportion of conductive agent in a double-layer distributed lithium-ion battery electrode according to any one of claim 7, characterized in that: The positive electrode active material of the battery is at least one of lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide and nickel cobalt manganese oxide; the negative electrode material of the battery is graphite, and the positive electrode collector of the battery is aluminum foil and the negative electrode collector is copper foil.

10. The method for determining the proportion of conductive agent in a double-layer distributed lithium-ion battery electrode according to claim 9, characterized in that: When preparing the positive electrode material of the battery, polyvinylidene fluoride is used as a binder, N-methyl pyrrolidone is used as a solvent, and at least one of acetylene black, carbon nanotubes and graphene is used as a conductive agent.